Electrolyte Changes in Malnourished under-5 Children with or without Diarrhoea (Journal of Shaheed Suhrawardy Medical College, 2021)
Background: Malnutrition is widely recognized as a major health problem in children in developing country. Malnutrition is a serious public health problem that has been linked to increase risk of morbidity and mortality .Many factors can cause malnutrition, most of which relate to poor diet, family size, family income, repeated ARI and diarrhea that may or may not causes electrolytes changes, particularly in underprivileged populations.Objective: To determine the serum electrolyte disturbances in malnourished under 5 children with or without diarrhea.Methodology: This is a descriptive study and conducted among 100 under 5 malnourished children of randomly selected in admitted patient of Dhaka Shishu Hospital. It was carried out during January-2015 to December-2017. They were suffering from different grades of malnutrition with or without diarrhea. On the basis of history, physical examination and anthropometrics measurement they were divided into Group A patients (n=56) who were malnourished but had diarrhoea and Group B patients (n=44) who were also malnourished and had no diarrhoea. Serum electrolytes were done in patients of both groups and the results were analyzed statistically by using SPSS windows programs 21.Results: Analysis of serum electrolytes in both groups that hyponatremia and hypokalemia were seen more frequently in patients of group A as compared to group B. In group A hyponatremia was seen in 41 patients (71.92%) while it was observed in 16 patients (28.07%) in group B (p